Impact of the Profit Margin Shares on the Islamic investment deposits Size: Sudan Case Study Between 2003 – 2016 - Fateh, MENNAA (Milev Journal of Research and Studies, 2020)
This study attempted to measure the impact of participation rate on investment deposits volume. The concept of participation rate and its most important formula and how it is applied in the Islamic economy were addressed In addition to the theoretical side, a statistical model was used to study the nature of the relationship between the two variables Under study through data derived from quarterly reports of Financial and economic proposals and the series of studies and research of the Central Bank of Sudan for the period 2003 to 2016. Where this model and hypotheses were tested using the least-squares method through the analysis of simple linear regression, the statistical spss 18 program was used to Construct the model, analysis the data and test the hypotheses. We concluded that a strong positive relationship exists between participation rate as an independent variable and the investment deposits size as a dependent variable according to the hypotheses presented. This study indicates that the rate of participation can be relied upon as a mechanism for monetary policy to influence the monetary mass at community.